An Evaluation of Buton Tengah Regent Regulation Number 26 of 2024 on Tuberculosis Control Using a PESTEL Analysis Framework - Rahma Fanti; Andi Marhana; Sitti Marzuqoh Aidah Basri; Yuli Budiyanti (Journal of Law, Social Science and Management, 2025)
Background: Tuberculosis (TB) remains one of the deadliest infectious diseases globally, with Indonesia ranking among the countries with the highest TB burden. In pursuit of TB elimination by 2030, Central Buton Regency enacted Regulation Number 26 of 2024 as a strategic regional policy to enhance TB control efforts. Objective: This study aims to evaluate the external factors influencing the implementation of this regulation, focusing on political support, funding allocation, social dynamics, technology utilization, legal frameworks, and environmental conditions. Method: Utilizing the PASTEL analytical framework (Politics, Economics, Sociology, Technology, Law, and Environment), this study assesses the effectiveness and challenges associated with the policy’s implementation. Results: Findings indicate that the regulation is grounded in a robust legal framework and aligns with national health policies. Nevertheless, key obstacles persist, including stakeholder coordination, sustainable financing, and the enduring social stigma surrounding TB patients. The integration of technology in health surveillance and patient monitoring shows promise in enhancing early detection and treatment outcomes. Furthermore, environmental determinants such as sanitation and population density significantly influence TB transmission, underscoring the need for policy integration with environmental health improvement initiatives. Conclusion: The successful implementation of Central Buton Regent Regulation Number 26 of 2024 depends on a comprehensive, multi-sectoral, and collaborative approach. Recommendations include strengthening inter-sectoral coordination, optimizing technological applications within health systems, and conducting educational campaigns to mitigate social stigma. Such a structured strategy is essential to effectively realize the goal of TB elimination by 2030. Keywords: Health Policy, Tuberculosis Prevention, Regional Regulation, Indonesia